The Human Park of Atlantis by Borislav Pekić - Ognjanović, Branka B. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper analysed different types of manipulation of human identity and development, the so-called anthropotechnics. This manipulation is described and analyzed as material – the creation of soulless robots, as well as spiritual – the creation of fictional and fragmentary identity of John Carver (Howland), which originated between the multiple layers of narrative and under the influence of the constant monitoring by the Atlanteans. The starting point of the analysis is the idea of a human park by Peter Sloterdijk. The human park is a result of anthropotechnics as well as a reference to the zoological park, in which the taming occurs. The purpose of the paper is to seek the answer to the question on the nature of the relation between humans and their creations which Pekić presents in his novel.